Smart And Inclusive Campus: Pengembangan Sarana dan Prasarana untuk Kampus Ramah Disabilitas - Cut Meuthia Rani; Zhilli Izzadati Khairuni; Yuslinda Yuslinda; Irene Santa Maria Simamora; Yunisah Putri Damanik (Universitas Medan Area, 2026)
Inclusive higher education in Indonesia still faces significant challenges in fulfilling the rights of persons with disabilities to access equal education. This article presents the concept of a